2013
DOI: 10.1179/2045772313y.0000000099
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of pharmacological replacement of melatonin for sleep disruption in individuals with tetraplegia

Abstract: In this pilot study, we were unable to show effectiveness of pharmacological replacement of melatonin for the treatment of self-reported sleep problems in individuals with tetraplegia. Trial Registration ClinicalTrials.gov # NCT00507546.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In any case, people with tetraplegia suffer sleep problems and poor quality of life [44]; moreover, these problems associated to the increased metabolic disorders (as described in the Introduction) place them in an increased risk for suffering stroke or myocardial infarction. Despite that a pilot clinical trial [45], carried out in eight patients with tetraplegia and absence of MT production, in which sleep disorders existed, showed that treating them with 8 mg of the MT agonist Ramelteon did not produce significant effects on the existing sleep problems, we think that the reported multiple beneficial effects of MT, and the absence of any adverse effect that it might produce, make this hormone useful when treating SCI patients. This is the reason by which we administered oral MT (at doses no lesser than 50 mg/ day) to any SCI patient being treated in the Medical Center Foltra.…”
Section: Discussionmentioning
confidence: 81%
“…In any case, people with tetraplegia suffer sleep problems and poor quality of life [44]; moreover, these problems associated to the increased metabolic disorders (as described in the Introduction) place them in an increased risk for suffering stroke or myocardial infarction. Despite that a pilot clinical trial [45], carried out in eight patients with tetraplegia and absence of MT production, in which sleep disorders existed, showed that treating them with 8 mg of the MT agonist Ramelteon did not produce significant effects on the existing sleep problems, we think that the reported multiple beneficial effects of MT, and the absence of any adverse effect that it might produce, make this hormone useful when treating SCI patients. This is the reason by which we administered oral MT (at doses no lesser than 50 mg/ day) to any SCI patient being treated in the Medical Center Foltra.…”
Section: Discussionmentioning
confidence: 81%
“…Some studies reported changes of the scores of SF-36 components after the administration of melatonin. Melatonin was reported to improve QOL, as assessed using the SF-36, in patients with primary insomnia and delayed sleep phase syndrome [48, 49], whereas no improvement in the QOL was observed in patients with tetraplegia and chronic fatigue syndrome [50, 51]. There have been no previous reports on the effects of ramelteon on health-related QOL of patients, regardless of diabetes; accordingly, this is the first report on the effect of ramelteon assessed using SF-36.…”
Section: Discussionmentioning
confidence: 99%
“…A small size pilot study71 and two subsequent randomized controlled, cross-over trials72,104 have demonstrated the safety of exogenous melatonin in tetraplegia. While the studies suggested some subjective improvements in sleep, both trials were underpowered statistically to demonstrate any effect on objective sleep variables.…”
Section: Management Of Sleep Disorders In Individuals With Scimentioning
confidence: 99%